Evaluation of Reed-Solomon (R-S) Coding performance for M-Ary modulation in AWGN and multipath fading channels - Syed Mohd. Dardin, Syed Mohd. Fairuz (2005)
In digital communication, Reed-Solomon (RS) codes refer to as a part of channel coding that had becoming very significant to better withstand the effects of various channel impairments such as noise, interference and fading. This signal processing technique is designed to improve communication performance and can be deliberate as medium for accomplishing desirable system trade-offs. As such, it is crucial that thorough evaluation on its performance is being carried out for justification. The purpose of this study is to evaluate the performance of RS coding system using M-ary modulation over AWGN and multipath fading channels. Rayleigh fading channel is used to represent the multipath fading channel and Multiple Frequency Shift Keying (MFSK) will be used as the modulation technique throughout this study. To achieve this, extensive simulation were performed by varying different type of parameters pertaining RS codes based on its characteristic. Computer simulation tool, MATLAB will be used to create and run extensively the entire simulation model for performance evaluation. It is discovered that the performance of RS codes can be assess through the function of its block size, redundancy and code rate and it is observed using Bir-Error Rate (BER) performance curve. Because RS codes work at byte level, thus it is also apparent that RS codes can perform well against burst noise. For more comprehensive study on RS Codes performance, different type of modulation techniques may be applied in the model and many other RS Codes with larger block sizes may be use.